ANALYSIS OF POSYANDU'S ROLE IN IMPROVING MOTHERS’ AWARENESS OF BALANCED NUTRITION FOR YOUNG CHILDREN - Rizqiyyah, Maya Fathiyyatur; Irawan, Teguh; Indriyani, Yulis; Mutiara; Zahra, Gisya Ainnaya; Nasywa, Jauzatu; Aqila, Hasna Labibah; Putri, Soffy Aura (Indonesian Journal of Health Science, 2025)
This study aims to analyze the role of Posyandu in increasing mothers' awareness of balanced nutrition in Rowosari Village. Using a descriptive qualitative approach, data were collected through in-depth interviews with 13 informants, consisting of 4 mothers of young children, 8 Posyandu cadres, and 1 midwife. The results of the thematic analysis based on role theory revealed five main indicators: role expectations, role performance, role pressures, role support, and evaluation-innovation. The findings indicate that Posyandu plays a crucial role as a center for community nutrition information and education; however, it faces challenges such as low mother participation, limited Posyandu cadres, insufficient training, and inflexible education schedules. Nevertheless, the cadres demonstrated initiative through practice-based educational innovations and digital approaches. This study emphasizes that the effectiveness of Posyandu is highly dependent on cross-sectoral support, cadre capacity, and contextual and interactive educational approaches.